Correction of storage ring optics with an improved closed-orbit modulation method - Xiaobiao Huang; Xi Yang (Physical Review Accelerators and Beams, 2023)
We improved a previously proposed method of using closed-orbit modulation for linear optics and coupling correction. Instead of fitting individual closed orbits, the improved method decomposes the orbit oscillation data into two orthogonal modes and fits the amplitudes of the modes at all beam position monitors. While the original method is limited to process around tens to a hundred orbits, the improved method can process thousands of orbits, which are easily available when alternating-current waveforms are applied to the two modulating correctors. The method has been experimentally demonstrated on the National Synchrotron Light Source (NSLS)-II storage ring.